Effectively Coping With Task Stress: A Study of the Validity of the Trait Emotional Intelligence Questionnaire–Short Form (TEIQue–SF). Issue 3 (4th May 2017) - O'Connor, Peter; Nguyen, Jessica; Anglim, Jeromy
ABSTRACT: In this study, we investigated the validity of the Trait Emotional Intelligence Questionnaire–Short Form (TEIQue–SF; Petrides, 2009) in the context of task-induced stress. We used a total sample of 225 volunteers to investigate (a) the incremental validity of the TEIQue–SF over other predictors of coping with task-induced stress, and (b) the construct validity of the TEIQue–SF by examining the mechanisms via which scores from the TEIQue–SF predict coping outcomes. Results demonstrated that the TEIQue–SF possessed incremental validity over the Big Five personality traits in the prediction of emotion-focused coping. Results also provided support for the construct validity of the TEIQue–SF by demonstrating that this measure predicted adaptive coping via emotion-focused channels. Specifically, results showed that, following a task stressor, the TEIQue–SF predicted low negative affect and high task performance via high levels of emotion-focused coping. Consistent with the purported theoretical nature of the trait emotional intelligence (EI) construct, trait EI as assessed by the TEIQue–SF primarily enhances affect and performance in stressful situations by regulating negative emotions.